Heat and fluid flow in electro-osmotically driven systems - Perumal Nithiarasu (Energy Procedia, 2017)
A numerical investigation of heat and fluid flow in electro-osmotically driven systems is presented, by considering plain channels and channels packed with charged solid particles. The results show that the introduction of charged solid particles a_ects the internal potential distribution, fluid flow and temperature distribution in the channel. Under the analysed conditions, the effect on heat transfer is confined to the centre of the channel. This topic needs to be further investigated since it is of interest in practical applications.